Conventional Approaches to Conflict Settlement and the Quest for Sustainable Peace in Afghanistan - Muhammad Ajmal Abbasi (ASIAN Journal of International Peace & Security (AJIPS), 2023)
In the contemporary global arena, the conflict spectrum has transformed substantially, with the phenomenon of inter-state wars being replaced by the intra-state violence as the predominant form of combat. Since the conflict paradigm is constantly evolving, especially with the increasing participation of diverse actors besides the nation states, so has been the corresponding evolution of the settlement mechanisms. However, Afghan conflict seems to have defied the widely accepted norms of conflict resolution diplomacy thus far, and the peace negotiations among the belligerents have mostly been taking place informally without any conventionally structured methodology. The departure of American-led-coalition forces resulted in the military takeover of Kabul by the Taliban, without any power sharing agreement through a formal conflict resolution mechanism. Thus, in the face of persistent internal fissures, discord as well as external intrigues, the peace and stability of Afghanistan would continue to be fragile without a consensual settlement process.